Project Report on Design of Microprocessor based System for Damping Measurement using Random Decrement Signature - CHANDRASHEKAR K M and SRINIVAS RAO S (1988)
INTERNAL GUIDE: NAGARAJ V, MVJCE EXTERNAL GUIDE: M R RM MURTHY, NAL
Keywords: Random Decrement Signature